Pengaruh Sistem Pembayaran Online dan Kompetensi Karyawan Terhadap Efisiensi Operasional PUDAM Tirta Bina Labuhanbatu (Jurnal Ekonomi Bisnis dan Akuntansi, 2025)
The advancement of technology in payment systems has brought significant changes to the world of business and public services, including at Perusahaan Umum Daerah Air Minum (PUDAM). This study aims to examine the influence of online payment systems and employee competence on operational efficiency at PUDAM Tirta Bina Labuhanbatu. The type of research used in this study is explanatory quantitative research, with data collection techniques conducted through questionnaires. The population in this study consists of employees working at PUDAM Tirta Bina Labuhanbatu with a minimum work experience of five months, and the sample used consists of 30 employees. The method employed consists of several statistical tests using SPSS version 30, including validity tests, reliability tests, multiple linear regression tests, the coefficient of determination test, t-test, and F-test to determine the relationship between variables. The results of the study indicate that the online payment system has a more dominant influence on operational efficiency compared to employee competence, as evidenced by a higher regression coefficient value. These findings suggest that the online payment system is a key factor in improving operational efficiency, supported by employees who are capable of managing the system effectively. Therefore, PUDAM Tirta Bina Labuhanbatu is recommended to continue developing its online payment infrastructure and enhancing employee training to optimize the effectiveness of the implemented system.